The mismatch between EFL/ESL teachers' beliefs and teaching practice: what is missing in the literature? - Tehrani, Hesam Tahsildar; Mohamed Razali, Abu Bakar; Kotamjani, Sedigheh Shakib; Neissi, Sina (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Language teacher beliefs play a significant role in research on language teacher professional development and teacher cognition. However, the literature on language teacher belief has persistently reported mixed findings about the congruence between what teachers state as their beliefs and their teaching performance. This paper, delineates the current contradictory research findings in terms of correspondence between belief and teaching practice, and concludes that the future research should adopt epistemic beliefs as the alternative to teacher beliefs as the research tool to elicit teacher beliefs. The author’s suggestion to replace teacher beliefs with teacher epidemic beliefs is assumed to render consistent correspondence between teacher beliefs and practice.